Profile of Critical Thinking Ability of Class VIII Junior High School Students in Science Learning on Simple Aircraft Materials - Sholikhah, Marathus; Dimas, Arifian (Science Education and Application Journal, 2022)
In this 21st-century educational paradigm, the ability to think critically is one of the life skills that must be possessed to adapt to an increasingly developing life. This study aims to describe the profile of the critical thinking ability of junior high school students in science subjects on Simple Aircraft material. The research method used is descriptive qualitative. Qualitative descriptive research is research that is used to investigate the actual data and is described in the form of words - words or verbally. The subjects in this study were students of class VIII-BIL SMP N 1 Sine with a total of 30 children. The research instrument used in the form of 10 reasoned multiple choice questions (two-tier multiple choice) based on indicators of critical thinking ability according to Facione which is divided into 4 namely (1) interpretation (2) analysis (3) inference (4) evaluation. The results of the study show that students have moderate critical thinking skills, with a percentage of 40%. Meanwhile, based on indicators showing aspects (1) Interpretation has a percentage of 72.3% with a high category (2) analysis has a percentage of 56.7% with a medium category (3) inference has a percentage of 47.8% with a low category (4) evaluation has a percentage 40% with low category. This research is expected to be used as a benchmark for teachers to provide a learning system that encourages students to improve their critical thinking skills by involving students in taking an active role in learning. In addition, this research is expected to provide a reference for similar research or further research.